Chế tạo vật liệu hấp phụ asen từ chitin bằng kỹ thuật polyme hóa ghép bức xạ - Hạnh, Trương Thị; Hiến, Nguyễn Quốc; Huy, Hà Thúc (Vietnam Journal of Chemistry, 2012)
Chitin with deactivation degree about 30-40% was irradiated up to dose of 28 kGy. Grafting 2,3-epoxypropyl methacrylate (EPMA) onto peroxidized chitin (EPMA-g-chitin) has been carried out at 80oC. The grafting was confirmed by Fourier transform infrared spectroscopy (IR) and scanning electron microscopy (SEM). The grafting degree was found to be dependent on the pre-irradiation dose and leveled off above 20 kGy. EPMA-g-chitin was treated with phosphoric acid (H3PO4) to open epoxy rings. Arsenic adsorption from solutions of Arsenate (Na2HAsO4) and groundwater samples onto phosphonated  EPMA-g-chitin has been investigated.